ANALISIS PENGARUH GROWTH COMPANY, FIRM SIZE DAN FINANCIAL DISTRESS BERDASARKAN METODE Z-SCORE TERHADAP PENERIMAAN GOING CONCERN OPINION ATAS KEMUNGKINAN TERJADINYA FORCED DELISTING SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Syukur Dermawan Halawa; Sri Wahyuni (UIR Press, 2017)
This study is aimed to examine the effect of growth company, firm size and financial distress based on Z-Score method on receipt of going concern opinion. The population of this study is manufature companies listed on the Indonesian Stock Exchange from 2013-2017. The sample of the study is all companies were selected by purposive sampling method. Based on the criteria, 27 companies were chosen as the samples of this study. This study used logistic regression analysis was used to test whether the independent variables affect the dependent variable. Data analysis for hypothesis test was done with Statistical Package for the Social Sciences (SPSS) version 23. The result of this study gives evidence that firm size and financial distress have a significant negative influence on receipt of going concern opinion on manufacturing companies during the period 2013-2017 and by that gives a probability on forced delisting. While growth company does not have a significant influence on receipt of going concern opinion on manufacturing companies during the period 2013-2017 and it means give a non-probability on forced delisting.